Pemberdayaan Nelayan melalui Inovasi Produk Olahan Ikan di Pulau Lembeh - Kadir, Arianto r; Grace M.A. Dengah; Melki Kumaat; Glen Oroh; Syafarudin (Bengkulu Institute, 2024)
The life of fishermen in Lembeh Island, North Sulawesi, still depends on daily catches that are highly influenced by weather and seasons. Limited knowledge of post-harvest processing and market access results in low selling prices for marine products. This community service program is designed to address these urgent needs, with the primary goal of enhancing the capacity and economic independence of fishermen through fish-based product innovation. The activities are conducted using a participatory needs-based approach, including technical training on processing fish into value-added products (such as fish floss, packaged smoked fish, and fish crackers), as well as business management and local marketing assistance. The process is carried out intensively and involves active participation from partners, particularly women fishermen's groups who play a key role in household businesses. The results show a significant improvement in processing skills and understanding of marketing strategies. Small-scale business units based on groups have also been formed, which have started independently selling products to local markets, coastal shops, and partner SMEs. This change not only increases income but also fosters self-confidence and a new sense of hope for the fishermen's families to build a better future from the sea on which they have long relied.